Human occupation and ecosystem change on Upolu (Samoa) during the Holocene. (20th January 2020) - Gosling, William D.; Sear, David A.; Hassall, Jonathan D.; Langdon, Pete G.; Bönnen, Mick N. T.; Driessen, Tessa D.; van Kemenade, Zoë R.; Noort, Kevin; Leng, Melanie J.; Croudace, Ian W.; Bourne, Anna J.; McMichael, Crystal N. H.
Abstract: Aim: To track the peopling of the South Pacific and assess their impact on terrestrial and aquatic ecosystems. Location: Upolu, Samoa. Taxon: Terrestrial and aquatic plants Methods: A sedimentary record covering the last c . 10, 500 years was recovered from the volcanic crater that contains Lake Lanoto'o near the centre of Upolu Island. Information on past ecological change was obtained from microscopic and macroscopic remains extracted from the sediments: charcoal (fire history), pollen/spores and plant remains (vegetation history), and lake status (algae/cyanobacteria). Information on the depositional environment and climate was obtained from geochemical and sedimentary analysis: loss‐on‐ignition (sediment composition), cryptotephras (volcanic eruptions) and precipitation regime (Ti/inc). The environmental history developed was compared with the archaeological record from the region. Results: Charcoal material was found in the Lake Lanoto'o sediments at higher abundances and more frequently in samples from the period after the first archaeological evidence of people on Upolu ( c . 2900–2700 years ago). No abrupt shift is recognized in the vegetation or aquatic ecosystem assemblages coincident with the arrival of people on the island. Main conclusions: Macrocharcoal is demonstrated to be an effective proxy for detecting human occupation of Upolu around 2, 800 years ago. The immediate impact of these settlers on the vegetation seems to have been minimal; however, a subsequent opening up of the landscape is suggested through the gradual increase in ferns. The absence of any significant change in the aquatic community associated with, or after, the arrival of people on the islands suggests that humans rarely visited the lake. We suggest that on Upolu a simple model of decreasing human impact away from coastal areas is applicable.